Financial Distress Determinants in Emerging Markets: Evidence from Nepalese Financial Institutions - Shrestha, Sajeeb Kumar; Mahat, Dipak; Neupane, Dasarath; Karki, Tej Bahadur; Acharya, Sabina (Darul Yasin Al Sys, 2025)
Background: Financial distress occurs when institutions fail to meet financial obligations, potentially leading to bankruptcy. While extensively studied in developed economies, research remains limited in developing nations like Nepal, where financial sector stability is crucial for economic growth. This study examines financial distress determinants in Nepalese financial institutions, focusing on liquidity, profitability, credit risk, firm size, operational efficiency (BOPO), and capital adequacy (CAR). Methods: A quantitative approach analyzed eight Nepalese financial institutions under regulatory scrutiny from 2018–2023. Panel data analysis, including unit root and Hausman tests, was conducted. The Fixed Effects Model (FEM) was selected, validated by a significant Hausman test (p = 0.0206). Altman’s Z-score measured distress, while regression analysis evaluated determinants. Results: Descriptive statistics revealed wide variations in financial health, with Altman’s Z-scores (0.1336–4.0317) indicating distress risks. Unit root analysis showed non-stationarity in liquidity, profitability, and credit risk, while firm size was stationary. CAR had a significant negative impact on distress (p = 0.011), whereas liquidity, profitability, and credit risk were insignificant. BOPO showed marginal significance (p < 0.1). The model exhibited strong explanatory power (R² = 0.9999) with no autocorrelation (Durbin-Watson = 2.2166). Conclusion: Capital adequacy is the most critical determinant of financial distress in Nepal, aligning with global findings but contrasting with studies emphasizing liquidity or profitability. The results underscore CAR’s role in mitigating distress, urging regulators to enforce robust capital standards. Novelty: This study fills a gap in Nepal-specific financial distress research, highlighting unique institutional dynamics. It challenges conventional liquidity-centric views, emphasizing CAR’s predictive superiority in emerging markets. Policymakers and managers can leverage these insights to enhance financial stability.